2022
DOI: 10.1002/advs.202203473
|View full text |Cite
|
Sign up to set email alerts
|

Induced Ferromagnetism in Epitaxial Uranium Dioxide Thin Films

Abstract: Actinide materials have various applications that range from nuclear energy to quantum computing. Most current efforts have focused on bulk actinide materials. Tuning functional properties by using strain engineering in epitaxial thin films is largely lacking. Using uranium dioxide (UO 2 ) as a model system, in this work, the authors explore strain engineering in actinide epitaxial thin films and investigate the origin of induced ferromagnetism in an antiferromagnet UO 2 . It is found that UO 2+x thin films ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Another factor that could potentially explain the difference lies in the presence of distinct variations in the stoichiometry of the UO 2 layer and/or the morphology of the UO 2 /Fe 3 O 4 interface. The former was shown [ 26 ] to be responsible for ferromagnetism in the UO 2+x thin films by incorporating point defects. Hence, the stoichiometry of the UO 2 layers was closely monitored after depositing each layer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another factor that could potentially explain the difference lies in the presence of distinct variations in the stoichiometry of the UO 2 layer and/or the morphology of the UO 2 /Fe 3 O 4 interface. The former was shown [ 26 ] to be responsible for ferromagnetism in the UO 2+x thin films by incorporating point defects. Hence, the stoichiometry of the UO 2 layers was closely monitored after depositing each layer.…”
Section: Resultsmentioning
confidence: 99%
“…(As a point of comparison: in the case of hyperstoichiometric UO 2+x thin film samples investigated in Ref. [26], the associated photoemission study documented in Ref. [35] indicated that the satellite peaks are scarcely visible).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…XRD, SEM–EDS, and FT‐IR were effectively utilized together to study uncommon copper alloy artifacts dating back to the eighth‐century BC and their complex degradation phenomena to develop strategies for long‐term conservation 7 . Finally, Raman is widely used to study paintings, especially pigments, dyes, and paints and deep UV Raman is especially valuable to characterize geologic, 8 oxide, 9 and paleontological specimens 10 …”
Section: Introductionmentioning
confidence: 99%